Portal decompression with transjugular intrahepatic portosystemic shunt prior to nonhepatic surgery: a single-center case series. Issue Volume 33:Issue S1(2021) (14th December 2020) - Goel, Ashish; Khanna, Amardeep; Mehrzad, Homoyon; Bach, Simon; Karkhanis, Salil; Kamran, Umair; Morgan, James; Rajoriya, Neil; Tripathi, Dhiraj
Abstract : Background and aims: Cirrhosis increases perioperative and postoperative mortality in nonhepatic surgery. Transjugular intrahepatic portosystemic shunt (TIPSS), by reducing portal pressure, may reduce intraoperative bleeding and postoperative decompensation. We report our experience of prophylactic TIPSS in nonhepatic surgery. Methods: Patients who underwent prophylactic TIPSS before nonhepatic surgery were identified from database with retrospective data collection via an e-patient record system. Primary outcome was discharged without hepatic decompensation after a planned surgery. Results: Twenty-one patients [age (median, range): 55, 33–76 years, Child's score: 6, 5–9] who underwent prophylactic TIPSS before nonhepatic surgery over a period of 9 years were included. All patients underwent successful TIPSS with a reduction in portal pressure gradient from 21.5 (11–35) to 16 (7–25) mmHg ( P < 0.001). Immediate post-TIPSS complications were seen in 7 (33%) patients including hepatic encephalopathy in four. Eighteen patients (86%) underwent planned surgical intervention. Significant postoperative complications included hepatic encephalopathy (3), sepsis (2) and bleed (1). Two patients died postoperatively with multi-organ failure. The primary outcome was achieved in 12 (57%) patients. Post-TIPSS portal pressure gradient was significantly higher in patients with the adverse primary outcome. Over a follow-up period of 11 (1–78) months; 1-, 6- and 12-months' survival was 90, 80 and 76%, respectively. Conclusion: Prophylactic TIPSS is associated with complications in up to one-third of patients, with 57% achieving the primary outcome. Careful patient selection in a multidisciplinary team setting is essential. Multicentre studies are necessary before the universal recommendation of prophylactic TIPSS.